Effect of PEG as a plasticizer on the electrical and optical properties of polymer blend electrolyte MC-CH-LiBF4 based films - Ahmed, Hawzhin T.; Jalal, Viyan J.; Tahir, Dana A.; Mohamad, Azhin H.; Abdullah, Omed Gh (Results in physics, 2019)
•PEG was used as a plasticizer to enhance ionic conductivity of MC:CH: LiBF4 polymer blend electrolyte films.•The highest ionic conductivity associated with the minimum activation energy at ambient temperature.•The lowest relaxation time for highest ion conductive sample indicates the faster ion dynamics.•The conduction mechanism for this system followed the overlapping large polaron tunneling (OLPT) model. Plasticized polymer blend electrolyte films based on methylcellulose (MC), chitosan (CH), lithium tetrafluoroborate (LiBF4), and polyethylene glycol (PEG) as a plasticizer were prepared and investigated. The effect of different concentrations of PEG was studied using AC impedance spectroscopy, and UV–Visible spectroscopy. The electrical and optical properties of polymer electrolytes have been improved upon addition of PEG. The DC conductivity was evaluated from the bulk resistance achieved from Nyquist impedance plots. Results from temperature studies reveal that all samples comply with the Arrhenius formula in the investigated temperature range. The sample with 10 wt% of PEG exhibits the highest ionic conductivity of 2.12×10-5S/cm with the minimum activation energy of 0.528eV at ambient temperature. The lowest relaxation time for highest ion conductive sample indicates the faster ion dynamics. The frequency-dependence AC conductivity was found to follows the Jonscher’s power law at various temperatures, and the conduction mechanism for this system followed the overlapping large polaron tunneling (OLPT) model. The increase in absorption and a decrease in optical band-gap in the UV region was confined by UV–Visible spectroscopy.